Feasibility of early mechanical circulatory support in acute myocardial infarction complicated by cardiogenic shock: The Detroit cardiogenic shock initiative. Issue 3 (20th December 2017) - Basir, Mir B.; Schreiber, Theodore; Dixon, Simon; Alaswad, Khaldoon; Patel, Kirit; Almany, Steven; Khandelwal, Akshay; Hanson, Ivan; George, Augustine; Ashbrook, Michael; Blank, Nimrod; Abdelsalam, Murad; et al.
Abstract: Objective: The 'Detroit Cardiogenic Shock Initiative' is a single‐arm, multicenter study to assess the feasibility of early mechanical circulatory support (MCS) in patients who present with acute myocardial infarction complicated by cardiogenic shock (AMICS) who undergo percutaneous coronary intervention. Methods: Between July 2016 and February 2017, 4 metro Detroit sites participated in the study. The centers agreed to treat patients with AMICS using a mutually agreed‐upon protocol emphasizing invasive hemodynamic monitoring and rapid initiation of MCS. Inclusion and exclusion criteria mimicked those from the 'SHOCK' trial with an additional exclusion criteria being use of intra‐aortic balloon pump counter pulsation prior to MCS. Results: A total of 41 consecutive patients were included. Patients had an average age of 65 ± 14 years, 71% were male and 59% of patients were admitted to the hospital in cardiogenic shock. Prior to receiving MCS, 93% of patients were on vasopressors or inotropes, 15% of patients had a witnessed out of hospital cardiac arrest, 27% of patients had an in‐hospital cardiac arrest, and 17% were under active cardiopulmonary resuscitation while MCS was being implanted. In accordance to the protocol recommendation, 66% of patients had a MCS device inserted prior to PCI. Right heart catheterization and hemodynamic monitoring was performed in 83% of patients. Door to support times averaged 83 ± 58 minutes and 71% of patients were able to reduce the levels of inotropes and vasopressors within the first 24‐hours of their index procedure. Pre‐procedure cardiac power output (CPO) was 0.57 W and post‐procedure CPO was 0.95 W, a 67% increase (p < 0.001). Survival to explant for the entire cohort was 85% a significant improvement from institutional historical controls (85% vs 51% p < 0.001) and survival to discharge was 76%. Conclusion: Centers who adopted a regional shock protocol emphasizing the delivery of early MCS with invasive hemodynamic monitoring can achieve rapid door to support times and can improve survival in patients who present with AMICS. Larger national studies will be needed to further validate this pilot feasibility study.